THE CORRELATION BETWEEN SELF-CONFIDENCE AND THE STUDENTS’ SPEAKING PERFORMANCE OF AMIK GLOBAL KENDARI - Normawati Normawati; Wa Muna (Langkawi: Journal of The Association for Arabic and English, 2015)
The correlation between self-confidence and the students’ speakingperformance. Thesis of Amik Global Kendari. The research aims finding outthe correlation between the students’ self-confidence and their speakingperformance. The method applied in this research was correlation itemployed of instrument namely questionnaire basic on indicators both ofthem. The questionnaire was used to find out the students’ self-confidenceand the students’ speaking performance. The population of the secondsemester, fourth semester and six semester students were 130 and the sampleconsisted of 30 students of Amik Global Kendari in academic year 2014-2015. The data collected by analyzed by using SPSS version 22, byconsulting with the standard of critical value (r) 5 % of significance and thenumber of sample (N) = 30. Participants’ mean score of self-confidence68.1333, and students’ speaking performance 67.2667 and participants’standard deviation of the students’ self-confidence 6.9063 and the students’speaking performance 6.61208, the sig. (2 tailed) 0.000 0.05, mean that thereis any positively significant correlation between students’ self-confidence andthe students’ speaking performance about 91.8 %, on sig. 95%.Keywords: Self-Confidence, Speaking Performance